2023
DOI: 10.1038/s41561-022-01117-8
|View full text |Cite
|
Sign up to set email alerts
|

Pacific shoreline erosion and accretion patterns controlled by El Niño/Southern Oscillation

Abstract: In the Paci c Basin, El Niño/Southern Oscillation (ENSO) is the dominant mode of interannual climate variability and drives substantial changes in oceanographic forcing, likely having a signi cant impact on Paci c coastlines. Yet, how sandy coasts respond to these basin-scale changes has to date been limited to a few long-term beach monitoring sites, predominantly on developed coasts. Here we use 35 years of Landsat imagery to map shoreline variability around the Paci c Rim (72,000 beach transects) and identif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 66 publications
1
30
0
Order By: Relevance
“…Lastly, the third and final metric we evaluate here is called “within C.I.” in Figure 10c, which represents the percentage of the time, during the “Hindcast (Validation)” period (2015–2020), that the model predicted shoreline position falls within the 95% confidence levels of the satellite‐derived shoreline observations, which are assumed to be identical to ±2εsat $\pm 2{\varepsilon }_{\text{sat}}$, where εsat ${\varepsilon }_{\text{sat}}$ is the 14 m RMSE derived at Ocean Beach (where dense GPS observations are available) and applied uniformly across the California coast. Although the uniform prescription of satellite‐error statistics is not ideal, we note that the general 10–15 RMS accuracy of satellite‐derived shorelines has been well established through extensive testing at many well‐monitored sites (e.g., Castelle et al., 2021; Hagenaars et al., 2017; Luijendijk et al., 2018; Pardo‐Pascual et al., 2018; Vos, Harley, et al., 2019; Vos et al., 2023). Figure 10c indicates that the model predictions are within the confidence intervals of the satellite observations approximately 95% of the time (on average) across California.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Lastly, the third and final metric we evaluate here is called “within C.I.” in Figure 10c, which represents the percentage of the time, during the “Hindcast (Validation)” period (2015–2020), that the model predicted shoreline position falls within the 95% confidence levels of the satellite‐derived shoreline observations, which are assumed to be identical to ±2εsat $\pm 2{\varepsilon }_{\text{sat}}$, where εsat ${\varepsilon }_{\text{sat}}$ is the 14 m RMSE derived at Ocean Beach (where dense GPS observations are available) and applied uniformly across the California coast. Although the uniform prescription of satellite‐error statistics is not ideal, we note that the general 10–15 RMS accuracy of satellite‐derived shorelines has been well established through extensive testing at many well‐monitored sites (e.g., Castelle et al., 2021; Hagenaars et al., 2017; Luijendijk et al., 2018; Pardo‐Pascual et al., 2018; Vos, Harley, et al., 2019; Vos et al., 2023). Figure 10c indicates that the model predictions are within the confidence intervals of the satellite observations approximately 95% of the time (on average) across California.…”
Section: Resultsmentioning
confidence: 99%
“…Since the 1980's, Earth‐observing satellites (e.g., the Landsat missions) have collected a massive archive of coastal imagery data that have only recently been leveraged for science and engineering applications (Turner et al., 2021). Recent advances in satellite remote‐sensing analysis provide a window into the recent past and current state of the world's beaches (Luijendijk et al., 2018) and their large‐scale vulnerability to climatic forces like El Niño (Vos et al., 2023). By leveraging the large streams of data offered from satellites, reduced‐complexity coastal‐change models seem poised for success in a challenging field of study owing to the newly found “treasure trove” of data (Barnard & Vitousek, 2023; Hunt et al., 2023; Vitousek et al., 2023a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rocky and inaccessible nature of this coast and the multi‐decade evolution of the accretion wave made remote sensing the most viable option for measuring the time‐dependent evolution of the region's shoreline. Thus, we used satellite‐based shoreline measurement techniques as a primary data source because these methods can characterize littoral‐scale phenomena over seasonal to decadal time scales (Bishop‐Taylor et al., 2021; Castelle et al., 2022; Jayson‐Quashigah et al., 2013; A. Luijendijk et al., 2018; Mentaschi et al., 2018; Sayre et al., 2019; Vos, Harley, et al., 2019; Vos, Splinter et al., 2019; Vos et al., 2023; Warrick, Vos, et al., 2022). We combine satellite‐based data with sediment transport theory and historical imagery, written and oral accounts, and maps to explore the unique evolution of this wave and provide new regional context and broader geophysical understanding that can be applied to other littoral systems.…”
Section: Introductionmentioning
confidence: 99%